A Radiographic Study to Investigate The Effect of Losing Posterior teeth in Bony Anatomical Changes In Tempromandibular Joint In Patients With Class II Kenndey (Journal of Hama University, 2022)
Introduction: Movements of the mandible depend on the anatomy of the teeth and the morphology of the tempomandibular joint far there is a correlation between the movements of the mandible and the morphology of the occlusion. It is necessary to understand the relation between these subjects if we need to make a physiological occlusion relations in case of rehabilitation.  Purpose: The aim of this research was to know if there is a correlation between the inclination of posterior part of articular eminence(AE) and losing of posterior teeth? Materials and Methods: sample included 24 tempomandibular joints of 12  of patients with Class II of Kennedy Classification to evaluate the inclination of articular eminence on the panoramic image. The Frankfort plane was determined by connecting the lowest point of the orbit (orbital point) with the uppermost point of the external auditory canal (porion point) of the same side. To sketch the posterior slope of the articular eminence, the deepest point of the mandibular fossa was connected with the outermost point of the articular eminence. The inclination of the posterior slope of the articular eminence in relation to Frankfort plane was measured as the angle of the intersection of those two lines to know the effect of the losing of posterior teeth in the articular eminence. Paired-Samples T Student test was made to compare between both sides.Results: The loss of the posterior teeth affect in increase of the flattering of the posterior part of the articular.Conclusions: There was a correlation between the losing of posterior teeth and the anatomical structure of the tempomandibular joint(AE)
Keywords: Tempomandibular Joint. Articular Eminence. Class II Kennedy. Posterior Teeth